The Role of the V/Brawijaya Regional Military Command in Overcoming the Spread of Covid-19 in East Java in the Context of Maintaining National Defense and Security - R. Fajar Grahananto; Susilo Adi Purwantoro; Herlina Juni Risma Saragih; Hikmat Zakky Almubaroq (CV. Rayyan Dwi Bharata, 2023)
This research discusses the role of the TNI under the Regional Military Command V/Brawijaya in preventing and breaking the chain of the spread of Covid-19 in East Java. The condition of the Covid-19 pandemic which has increased involves many actors and many elements in handling it, including the military. Military involvement is carried out in the context of Military Operations Other Than War (OMSP) as stipulated in Law Number 34 of 2004 concerning the TNI. The research design uses a qualitative approach, where the approach in this study produces descriptive data in the form of literature or writing and behavior that can be observed from the subject itself. The literature reviewed is used to answer questions about the research problems being carried out. In addition, it uses a literature study approach, namely research that uses library materials without conducting field research, so that its activities are related to methods of collecting library data, reading, recording and processing research materials into a formulation of the research results expected by the research objectives. carried out by Kodam V/Brawijaya as an effort to prevent and break the chain of Covid-19 in the people of East Java. Kodam V/Brawijaya and its staff as a defense component in East Java Province optimally handle Covid-19 with cooperation, collaboration and synergy of all elements in East Java to maintain national defense and security.